Mesoporous lignite-coke as an effective adsorbent for coal gasification wastewater treatment. Issue 1 (7th December 2016) - An, Hongguang; Liu, Zhenqiang; Cao, Xiaoxin; Teng, Jilin; Miao, Wenhua; Liu, Junfeng; Li, Ruozheng; Li, Peng
Abstract : Mesoporous lignite-coke as an effective adsorbent for high molecular weight refractory compounds in coal gasification wastewater treatment. Abstract : This paper introduces a novel adsorbent lignite coke (LC), which is suitable for macromolecular contaminant removal in coal gasification wastewater. Adsorption results show that LC had higher decolorization ability and removed more refractory compounds than activated carbons (ACs), and can improve wastewater biodegradability. Pore size distribution and electron microscopy results show that LC had more mesopores than ACs, which supplied enough area for high molecular weight pollutant removal. Equilibrium adsorption isotherms show that LC had high affinity with pollutants in coal gasification wastewater.